Fixed Point Theorems for Cyclic Contractions in C⁎-Algebra-Valued b-Metric Spaces - Chakkrid Klin-eam; Prondanai Kaskasem (Journal of Function Spaces)
We study fundamental properties of C⁎-algebra-valued b-metric space which was introduced by Ma and Jiang (2015) and give some fixed point theorems for cyclic mapping with contractive and expansive condition on such space analogous to the results presented in Ma and Jiang, 2015.